C1q A08 Is a Half-Cryptic Epitope of Anti-C1q A08 Antibodies in Lupus Nephritis and Important for the Activation of Complement Classical Pathway - Wu, Wen-Jun; Tan, Ying; Liu, Xiao-Ling; Yu, Feng; Zhao, Ming-Hui (Frontiers in Immunology, 2020)
To investigate the fine epitope(s) of anti-C1q A08 antibodies and their roles in complement activation in lupus nephritis, C1q A08 and related peptides with various amino acid sequences around A08 were synthesized. Anti-C1q A08 antibodies from 10 lupus nephritis patients were purified from plasmapheresis samples, and four monoclonal antibodies against C1q A08 were screened and identified from mouse hybridoma cells, to study the fine epitope(s) of C1q A08 using ELISA and Biolayer Interferometry (BLI). The biofunction of anti-C1q A08 antibodies for complement classical pathway activation was investigated by C3 activation assay. Anti-C1q A08 antibodies and anti-C1q antibodies were also detected in the sera of female BALB/C mice immunized by C1q A08 peptides. None of the anti-C1q A08 antibodies, which were affinity purified from the 10 lupus nephritis patients, could bind intact C1q coated on microtitre plates, neither could the anti-C1q antibodies bind to C1q A08 peptides coupled on resin, indicating that the human anti-C1q antibodies and anti-C1q A08 antibodies may recognize different epitopes of C1q. One of the four C1q A08 mAbs (32-4) bound to the six amino acids of N-terminus of C1q A08, while another C1q A08 mAb (17-9) bound to eight or 10 amino acids of C-terminus of A08. The third and fourth C1q A08 mAb (1A12 and 4B11) bound to the whole sequence of A08. Only 32-4 mAb bound to the intact C1q coating on an ELISA plate, whereas 17-9 mAb, 1A12 mAb, and 4B11 mAb could not. However, using a BLI assay, 17-9 mAb, 1A12 mAb, and 4B11 mAb, but not 32-4 mAb, could bind to intact C1q. Furthermore, 1A12 mAb and 4B11 mAb, but not 32-4 and 17-9 mAb, could inhibit the activation of complement classical pathway. Anti-C1q A08 antibodies were detected in all the female BALB/C mice in the experimental group but not in the control group. Two out of six in the experimental group developed anti-C1q antibodies. C1q A08 is a half-cryptic epitope of C1q involving N-terminal six amino acids of C1q A08, and this is important to the activation of a complement classical pathway, and some anti-C1q A08 antibodies were able to prevent this process. Epitope spreading of C1q occurred in the mice immunized with C1q A08 peptides.